2016
DOI: 10.1002/elps.201600329
|View full text |Cite
|
Sign up to set email alerts
|

On the ionic strength dependence of the electrophoretic mobility: From 2D to 3D slope‐plots

Abstract: Determining the charge and the nature (small ion, nanoparticle, or polyelectrolyte) of an unknown solute from its electrophoretic characteristics remains a challenging issue. In this work, we demonstrate that, if the knowledge of the effective electrophoretic mobility (μ ) at a given ionic strength is not sufficient to characterize a given solute, the combination of this parameter with (i) the relative decrease of the electrophoretic mobility with the ionic strength (S), and (ii) the hydrodynamic radius (R ), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Whatever the nature of the solute (small ion, oligomers, polyelectrolyte, nanoparticle), it was shown that eq. (5) is verified (within a 5% error margin) between typically 1 and 100 mM ionic strength [34]. Such plots have the advantage to quantify the dependence on ionic strength and to possibly interpolate the effective mobility values at any ionic strength.…”
Section: Ionic Strength Dependence and Slope Plot Approachmentioning
confidence: 59%
See 2 more Smart Citations
“…Whatever the nature of the solute (small ion, oligomers, polyelectrolyte, nanoparticle), it was shown that eq. (5) is verified (within a 5% error margin) between typically 1 and 100 mM ionic strength [34]. Such plots have the advantage to quantify the dependence on ionic strength and to possibly interpolate the effective mobility values at any ionic strength.…”
Section: Ionic Strength Dependence and Slope Plot Approachmentioning
confidence: 59%
“…This behavior can explain the inversion in migration order between ACH oligomers and sodium. The impact of ionic strength on ACH oligomers migration will be discussed in more detail in a subsequent section using the recently developed slope plot approach [34,35]. It can be also noticed from Fig.…”
Section: Influence Of the Bge Ionic Strength At Constant Phmentioning
confidence: 96%
See 1 more Smart Citation
“…These figures of merit are very useful for estimating the impact of the ionic strength on the effective mobility and for the modeling of the effective and apparent selectivities according to f and I, as discussed in the next section. The S values are also very informative about the characteristics of the solute (charge, nature, or size) [25,26,27]. As a matter of comparison, proteins have typical S values between 0.3 and 0.4 [27], which are very similar to the values obtained for moderately charged PAMAMPS with 30% ≥ f ≥ 10%.…”
Section: Resultsmentioning
confidence: 85%
“…Indeed, it is a very general trend in electrophoresis that for any solutes (small ion, polyelectrolyte, proteins, and nanoparticles), the effective mobility is a decreasing function of the ionic strength. 43,47,48 Figure 5A displays the mobility ratio R as a function of ACH concentration. Clearly, the R values are much higher for BSA (typically between 4.4 and 9.7) than for LSZ (0.7 to 1.6) suggesting much higher interaction of BSA with ACH compared to LSZ.…”
Section: Resultsmentioning
confidence: 99%